(3GSJJGQ GdEUeGe (B((3aj GdOYhI GdaGWejI(B)s - (3CHh eMeO GdfjSGHhQj , CMeO Hf EHQGgje, CHh eMeOs
(3ChdgG (B:s
(3GdMeO ddg MeOkG cKjQkG ceG gh Cgdg heSJMbg CYde Ydec Gddg GdQTO Cfg hd eG abO GdEeGe Ydjg hHbi GdOYGI s
(3BNQgG (B:s
(3hNQL GdegOi UdhGJ Gddg Ydjg hhdOg hcGf ef CeQg eGgh eOhf eYQha s
(3Vef eLehY , JQJjHgG (B: (3ef U (B10 - (3U(B15s
(3GfXQ GdbSe GdKGdK HQbe (B881s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B325 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B27 s
Keywords: (3GdJGQjNs